Kajian Yuridis Normatif terhadap Pertanggungjawaban Hukum Platform Telegram dalam Pembajakan Film Berdasarkan Hukum Hak Cipta di Indonesia - Gina Rahma; Tiara Kansa Anjar Pratiwi; Asfy Putri; Ikhwan Aulia Fatahillah (Media Hukum Indonesia (MHI), 2026)
This study examines the legal liability of the Telegram platform for film piracy under Indonesian copyright law, addressing the persistent gap between existing legal norms and their enforcement in the digital environment.The research employs a normative legal method using statutory and conceptual approaches, relying on secondary data derived from legislation, legal doctrines, and relevant literature. The findings indicate that Indonesia’s legal framework, including copyright and electronic transaction regulations, is substantively comprehensive in protecting the economic rights of creators and regulating digital platforms. However, enforcement remains ineffective due to technological complexities, limited monitoring capabilities, weak deterrent effects, and low public awareness. The study further reveals that Telegram, while not the primary perpetrator, may bear civil liability in the form of secondary liability if negligence in preventing or addressing infringing content is proven, although criminal liability is difficult to establish without evidence of intent.